OPT3 Is a Phloem-Specific Iron Transporter That Is Essential for Systemic Iron Signaling and Redistribution of Iron and Cadmium in Arabidopsis . Issue 5 (27th May 2014) - Zhai, Zhiyang; Gayomba, Sheena R.; Jung, Ha-il; Vimalakumari, Nanditha K.; Piñeros, Miguel; Craft, Eric; Rutzke, Michael A.; Danku, John; Lahner, Brett; Punshon, Tracy; Guerinot, Mary Lou; Salt, David E.; et al.
Abstract : This work identifies a physiological substrate and a physiological function of the Arabidopsis oligopeptide transporter, OPT3, in iron (Fe) homeostasis, provides a mechanistic explanation of the role of OPT3 in systemic Fe signaling, and uncovers an aspect of crosstalk between Fe homeostasis and cadmium partitioning. Abstract: Iron is essential for both plant growth and human health and nutrition. Knowledge of the signaling mechanisms that communicate iron demand from shoots to roots to regulate iron uptake as well as the transport systems mediating iron partitioning into edible plant tissues is critical for the development of crop biofortification strategies. Here, we report that OPT3, previously classified as an oligopeptide transporter, is a plasma membrane transporter capable of transporting transition ions in vitro. Studies in Arabidopsis thaliana show that OPT3 loads iron into the phloem, facilitates iron recirculation from the xylem to the phloem, and regulates both shoot-to-root iron signaling and iron redistribution from mature to developing tissues. We also uncovered an aspect of crosstalk between iron homeostasis and cadmium partitioning that is mediated by OPT3. Together, these discoveries provide promising avenues for targeted strategies directed at increasing iron while decreasing cadmium density in the edible portions of crops and improving agricultural productivity in iron deficient soils.